High-performance dual-mode extended SWIR photodetector based on p-WSe2/graphene/n-Ge p-g-n heterostructure - Haokun Ding; Xinyue Zhang; Long Zhang; Guangyang Lin; Cheng Li (APL Materials)
Mixed-dimensional van der Waals (vdW) heterostructures based on two-dimensional materials and three-dimensional semiconductors not only offer high-quality interfaces and flexible tunable band alignments but also exhibit excellent compatibility with complementary metal–oxide–semiconductor (CMOS) technology. These attributes make such heterostructures particularly promising for developing broadband, high-sensitivity, and high-speed photodetectors. In this work, we demonstrate a high-performance broadband photodetector based on a p-WSe2/graphene (Gr)/n-Ge p-g-n vdW heterostructure, capable of operating across the 400–2400 nm wavelength range, which can be switched between photodiode (PD) and heterojunction phototransistor (HPT). The shortwave infrared response range is extended to 2400 nm through photoemission between Gr and the conduction band of the p-WSe2/n-Ge heterojunction. The device has higher responsivity in PD mode while responding faster with lower dark current in HPT mode. In PD mode, the device exhibits enhanced responsivity due to carrier multiplication in Gr facilitated by the built-in electric field and the photogating effect from the interface of heterojunction, yielding responsivities of 652 and 275 A W−1 at 405 and 1550 nm, respectively. In HPT mode, the forward-biased vdW heterojunction emitter generates significant photocurrent gain due to a high hole/electron injection ratio, while the n-Ge/Pt Schottky barrier collector effectively suppresses the dark current. The remarkable responsivity of 11 and 118 A W−1 with fast response times of 150 and 210 µs is achieved at 405 and 1550 nm, respectively. These tunable operation modes offer versatility for various application scenarios. In addition, the proposed structure provides an alternative strategy for developing high-performance, low-cost, and CMOS compatible broadband photodetectors.